Specificity of receptor-mediated recognition of malondialdehyde-modified low density lipoproteins. - Haberland, M E (1982)
Blood-borne human monocytes and macrophages derived from human monocytes in vitro express an active low density lipoprotein (LDL) receptor and an active receptor for negatively charged proteins, the scavenger receptor. When less than 15% of the lysine residues of human LDL were modified by malondialdehyde while the lipoprotein was in solution, recognition and uptake of the modified lipoprotein occurred via the LDL receptor. Further modification resulted in threshold recognition and uptake by the scavenger receptor with concomitant loss of recognition by the LDL receptor. The rate of degradation via the LDL receptor pathway was inversely related to the degree of modification whereas that mediated by the scavenger receptor was independent of the extent of incorporation of malondialdehyde once threshold recognition was achieved. In contrast to the interaction of LDL with malondialdehyde in solution, modification of less than 15% of the lysine residues of LDL adsorbed to heparin-Sepharose resulted in recognition and uptake by the scavenger receptor. The scavenger receptor-mediated uptake of malondialdehyde-modified LDL may be dependent on formation of recognition sites involving specific modified lysine residues or changes in the conformation of LDL induced by neutralization of specific lysine residues of the apoB polypeptides or both.